Topical Fluoride for Prevention of Dental Caries: A Review - Padmaja Nayak (Institute of Medico-legal Publications Pvt Ltd, 2020)
Topical Fluoride has been the primary human action of dental caries hindrance for many decades. There arevarious mechanisms that kind it advantageous including inhibiting pathology, enhancing remineralization,and inhibiting microorganism maturation. This paper represents the development, mechanism of action, andmanner of use of various fluoride products. The comparative study between the different forms of fluoridepreparation is over viewed here. Fluoride toothpaste, mouth rinses, varnishes are some of the productsusually utilized for caries prevention. The practician must ascertain sort of topical preparation suitable fordifferent types of patients who are at different risk levels.